Initial Steps in Implementing the Managing Director's Action Plan for the 2014 Triennial Surveillance Review. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
In November 2014, the Managing Director set out a five-year Action Plan for Strengthening Surveillance in line with the goals of the 2014 Triennial Surveillance Review (TSR). In response to Executive Directors' request for an early update, this report outlines the initial steps taken to operationalize the Action Plan. Many initiatives will take time to be fully embedded in the Fund's surveillance products and its day-to-day dialogue with member countries. This initial phase focused on putting in place the building blocks to support teams engaging in surveillance. This includes revising guidance to staff in line with the TSR priorities, investing in tools and staff training to boost capacity, and revamping work practices. Ongoing engagement among staff will be critical, both to raise awareness and to understand the issues teams are facing. Managers will play a vital role in implementing changed work practices, and the new leadership framework will support this. While not all initiatives are equally advanced given their different starting points or varying complexity, work is moving forward in all three of the broad pillars of the TSR: Deepening risk and spillover analysis. Staff is making a concerted effort to develop new approaches to macrofinancial surveillance, including through area department led pilot cases, enhanced technical support from functional departments, and a more collaborative approach to build skills and share knowledge. More tailored and expert policy advice. To better adapt our advice to the changing needs of member countries, staff is laying the groundwork for more detailed and tailored macro-structural analysis and ensuring that our fiscal advice continues to be 'state of the art'. Efforts to leverage cross-country experience have gained momentum. Achieving greater impact. Staff is promoting more client focused communication, including exploring ways for more effective two-way dialogue with member countries, and promoting greater clarity in its multilateral messages. Staff is also developing principles to better understand and address perceptions of evenhandedness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Area Department; Department; MCD; Policy; PP